Variation of reservoir fluid property during the high pressure air injection process. Issue 2 (26th January 2016) - Li, Yi-Bo; Pu, Wan-Fen; Zhao, Jiang-Yu; Zhao, Qi-Ning; Sun, Lin; Jin, Fa-Yang; Zhao, Jin-Zhou; Zhou, Wei
ABSTRACT: This research aimed at determining the variation of reservoir fluid property during the high-pressure air injection process. For this purpose, the forward multiple contact experiment was employed by pressure–volume–temperature (PVT) system to investigate the physical property variation of the crude oil and the complex oxidation reactions. The results show: under the relative low temperature and pressure condition, instead of carbon dioxide, carbon monoxide dominates the products in the air phase. The gas/oil ratio and volume ratio increased due to the generated gas while the viscosity and density achieved a descending trend. The colloid and bitumen in the oil phase reduced by half but the amount of wax achieved a small increase. The low-temperature oxidation and pyrolysis reactions caused the fluctuated change of the different compounds. The amount of light compounds decreased at the beginning and then increased while that of heavy compounds showed the opposite trend. But at last, due to the H/C ratio, the light compounds increased to more than their initial value.